2018
DOI: 10.1038/s41467-018-05976-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into Vibrio cholerae’s intra-amoebal host-pathogen interactions

Abstract: Vibrio cholerae, which causes the diarrheal disease cholera, is a species of bacteria commonly found in aquatic habitats. Within such environments, the bacterium must defend itself against predatory protozoan grazers. Amoebae are prominent grazers, with Acanthamoeba castellanii being one of the best-studied aquatic amoebae. We previously showed that V. cholerae resists digestion by A. castellanii and establishes a replication niche within the host’s osmoregulatory organelle. In this study, we decipher the mole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 78 publications
0
51
0
Order By: Relevance
“…TfoY also induces the T6SS of V. cholerae , though the TfoX and TfoY regulons are nonoverlapping, with TfoX co‐inducing competence and TfoY orchestrating a defensive reaction. This defensive reaction includes enhanced motility and the co‐production of the T6SS with additional extracellular enzymes, some of which are known to intoxicate amoebal predators (Metzger et al ., ; Van der Henst et al ., ). Moreover, TfoX is naturally produced upon growth on chitinous surfaces (Meibom et al ., ), while TfoY production is inhibited by c‐di‐GMP, an secondary messenger in bacteria, such that it is only present at low intracellular c‐di‐GMP levels (Inuzuka et al ., ; Metzger et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TfoY also induces the T6SS of V. cholerae , though the TfoX and TfoY regulons are nonoverlapping, with TfoX co‐inducing competence and TfoY orchestrating a defensive reaction. This defensive reaction includes enhanced motility and the co‐production of the T6SS with additional extracellular enzymes, some of which are known to intoxicate amoebal predators (Metzger et al ., ; Van der Henst et al ., ). Moreover, TfoX is naturally produced upon growth on chitinous surfaces (Meibom et al ., ), while TfoY production is inhibited by c‐di‐GMP, an secondary messenger in bacteria, such that it is only present at low intracellular c‐di‐GMP levels (Inuzuka et al ., ; Metzger et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The T6SS of pandemic V. cholerae is silent under standard laboratory conditions (Pukatzki et al, 2006). In contrast to pandemic strains, the O37 serogroup strains V52 and ATCC25872 are toxigenic but nonpandemic and their T6SS is constitutively activated, as is the case for most environmental isolates (Pukatzki et al, 2006;Unterweger et al, 2012;Bernardy et al, 2016;Van der Henst et al, 2018). To explain the differences in T6SS activity and to provide insight into the T6SS's biological functions, it is, therefore, important to understand the underlying regulatory pathways in pandemic V. cholerae strains.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that lipases similar to VPA0226 can esterify cholesterol by the transfer of an acyl group from an acyl-containing lipid to cholesterol thereby converting free cholesterol to a cholesteryl ester (16, 17). It should be noted that only the lipase activity, but not the transferase activity, has been observed previously for Vibrio lipases (14, 18). To confirm lipase activity of VPA0226, we tested this enzyme with the EnzChek® Phospholipase A2 (PLA2) Assay Kit (Invitrogen).…”
Section: Resultsmentioning
confidence: 65%
“…Recombinant VvhA from Vibrio vulnificus was shown to induce NF-κB-dependent mitochondrial cell death mediated by the production of lipid raft-dependent ROS (31). Another structural homologue lec / VC_A0218 in V. cholerae with lipase activity is implicated in escape from the infected amoeba (18). In addition, a genetically non-homologous but functionally similar TgLCAT, lecithin: cholesterol acyltransferase encoded by a protozoan parasite Toxoplasma gondii is also implicated in host cell egress (32).…”
Section: Discussionmentioning
confidence: 99%
“…Cholera infections are typically caused by contaminated food and water 23,24 . Seven cholera pandemics have been recorded in modern history and the latest is still ongoing 25,26,27 . V. cholerae life cycle is marked by repetitive transitions between aquatic environments and the host gastrointestinal tract, thus it has to adjust to different qualities and quantities of nutrient sources 28 .…”
Section: Introductionmentioning
confidence: 99%